Pengaruh Disiplin Dan Motivasi Kerja Terhadap Peningkatan Kinerja Pegawai Fakultas Ilmu Keolahragaan Dan Kesehatan Universitas Negeri Jakarta: The Influence of Discipline and Work Motivation on Improving Employee Performance at the Faculty of Sports Science and Health, Jakarta State University - Purwati Purwati; Tri Lestari (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
The research was conducted at the Faculty of Sports and Health Sciences, State University of Jakarta. This study aims to examine the influence of discipline and work motivation on employee performance at FIKK UNJ both partially and simultaneously, in order to support the improvement of organizational effectiveness and productivity. The approach used was quantitative with the survey method, data was collected from 53 respondents through questionnaire deployment and analyzed using multiple linear regression techniques with the help of SPSS software version 25. The results of the research on the discipline variable had a partial significant effect on employee performance with a calculated value of 4,581 > a table of 2,007 and a significant of 0.000 < 0.05, then the first hypothesis (H1) was accepted. The work motivation variable had a partial significant effect on employee performance with a calculated value of 7,899 > 2,007 and a significant of 0.000 < 0.05, then the second hypothesis (H2) was accepted. The variables of discipline and work motivation had a simultaneous significant effect on employee performance with a calculated value of 126,781 > a table of 3.18 and a significant value of 0.000 < 0.05, then the third hypothesis (H3) was accepted. Based on the results of the R-Square coefficient of determination test (R2), it is known that 83.5% of the bound variables, namely employee performance, can be influenced by independent variables, namely discipline and work motivation. While the remaining 16.5% was influenced by other variables that were not studied in this study